Comparative Studies of Two Nigerian Ecotypes Chicken Kept in Battery Cages for Laying Performance and Egg Quality Traits - F. E, Sola-Ojo; K. L, Ayorinde; A. A, Toye; O. M, Jatto (Asian Journal of Agriculture and Rural Development, 2013)
This study was conducted to evaluate and determine the effects of ecotype on laying performance and some egg quality traits of two indigenous chickens ecotype in Kwara state Nigeria Fulani Ecotype chicken (FE) and Yoruba Ecotype chicken (YE) kept in battery cage for a period of fifty two (52) weeks. It was observed that the YE matured earlier than FE with Age at First Egg (AFE) of 20.56 (20 – 23weeks) compared to 26.73weeks (22-31wks) obtained for FE. Significant difference (p<0.05) existed between their body weight at first egg, (BFE) with FE significantly bigger 1437.5g than the YE 1314.60g. The mean Egg weight (EW), Total Egg Number (TEN), Hen House Production (HHP) in FE were 44.11g, 128 and 53.16%, and significantly (p<0.05) higher than 42.44g, 98, 45.50% obtained for YE, the differences between these parameters were significant (p<0.05). YE had a lower clutch size (CS) of 2- 6 eggs per clutch and a longer pause length (PL) of 1- 6 days while the FE had a larger Clutch size of 3-9 eggs per clutch and a shorter pause length of 1-3 days. External and internal quality traits of eggs from both ecotypes were similar except shell thickness that was significantly (p<0.05) better in the YE and yolk height that was significantly (p<0.05) higher in FE. The results of this finding indicated a marked difference in laying performances of the two indigenous chickens, yolk height and shell thickness and no significant (p>0.05) differences in other egg quality traits measured.